GERAKAN SOSIAL MASYARAKAT PETANI DI NAGARI KETAPING - Yuhasnil Yuhasnil (Alhurriyah, 2010)
This research describes about the movement of social or protests that done by farmer in Nagari Ketaping Kab. Padang Pariaman in claming the justice and also the resistance to the arbitrary of government officer to small society. This research is done by qualitative method and follow the ethnography steps which suggested by Spradley. The data is colleted by in-depth interviewing, observation, and documentary study. The informant is chosen by using snow ball technique. The result of this research shows that the social movement of farmer in Nagari Ketaping represents the long efforts of farmer in Indonesia. Goverments’ attitude in handling this case makes the farmer society feel uncomfortable and try to do actions by building public opinion. Farmer society tise to ask supports from other institution, like : Institute Legal Aid (LBH), Institude Research of Advocacy (LRA), and Environments’ Association (WALHI).